AFRICAN RHYTHM AND AFRICAN SENSIBILITY, AESTHETICS AND SOCIAL ACTION IN AFRICAN MUSICAL IDIOMS by John Miller Chernoff, University of Chicago Press, Chicago and London, 1979, pp. 261, photographs, $20.00. - Tracey, Andrew (International Library of African Music, 1983)
pages: 121-123
Keywords: African Music